WAYS TO USE APHORISMS IN THE CULTIVATION OF SPEECH OF JUNIOR SCHOOL PUPILS - Mohroy Mukhtariy Sodirzoda (Galaxy International Interdisciplinary Research Journal, 2021)
Speech has two forms –oral and written speech. Although these are intertwined, each has its own characteristics. In oral speech, sounds, when words are pronounced through speech, are perceived through the auditory organs. Therefore, in the cultivation of oral speech by students, we must first find out the reasons for the shortcomings in their speech, looking for ways to eliminate it.